Sex‐specific differences in GABAA‐benzodiazepine receptor availability: relationship with sensitivity to pain and tobacco smoking craving. (21st February 2012) - Esterlis, Irina; McKee, Sherry A.; Kirk, Kathryne; Lee, Dianne; Bois, Frederic; Stiklus, Stephanie M.; Seibyl, John P.; Krishnan‐Sarin, Suchitra; O'Malley, Stephanie S.; Staley, Julie K.; Cosgrove, Kelly P.
ABSTRACT Sex differences exist in tobacco smoking behaviors. Nicotine, the primary addictive ingredient in tobacco smoke, indirectly affects γ‐amino butyric acid (GABA) function. Previous studies reported sex‐by‐smoking interactions in brain GABA levels. The goal of the present study was to evaluate if there is a sex‐by‐smoking interaction at the GABAA‐benzodiazepine receptors (GABAA‐BZRs), as well as relationships between GABAA‐BZR availability and behavioral variables before and after 1 week of smoking cessation. Twenty‐six women (8 non‐smokers, age 36.0 ± 13.4 years; 19 smokers, age 34.6 ± 8.9 years) and 25 men (8 non‐smokers, age 37.9 ± 13.8 years; 17 smokers, 34.1 ± 12.4 years) were imaged using [123I]iomazenil and single‐photon emission computed tomography. Smokers were imaged at baseline 7 hours after the last cigarette. A significantly great number of men were able to abstain from smoking for 1 week (P = 0.003). There were no significant differences in nicotine dependence and cigarette craving, mood or pain sensitivity between male and female smokers. There was a significant effect of gender across all brain regions (frontal, parietal, anterior cingulate, temporal and occipital cortices, and cerebellum; P < 0.05), with all women (smokers and non‐smokers combined) having a higher GABAA‐BZR availability than all men. There was a negative correlation between GABAA‐BZR availability and craving (P ≤ 0.02) and pain sensitivity (P = 0.04) in female smokers but not male smokers. This study provides further evidence of a sex‐specific regulation of GABAA‐BZR availability in humans and demonstrates the potential for GABAA‐BZRs to mediate tobacco smoking craving and pain symptoms differentially in female and male smokers.